Increasing the Welfare of Salted Fish MSME Actors Through Innovation, Branding, and Product Digital Marketing - Aulia, Destanul; Kurniawan Z, Teguh; Luthfiyyah, Suci Haya; Hutasuhut, Raihan Putri Dahlina; Azahra, Siti; Deannova, Alfito (Talenta Publisher, 2023)
MSME stands for micro, small and medium enterprises run by individuals and small business entities. Business development by MSMEs aims to build a national economy based on a just economic democracy. MSMEs play an important role in the Indonesian economy by expanding opportunities and employment, increasing the Gross Domestic Product (GDP), and providing a safety net, especially for people with low incomes to carry out productive economic activities. Therefore, there is a need for support for improving the welfare of MSMEs. Denai Bird's Nest as part of Deli Serdang Regency which is located in a coastal area, most of the villagers use processed marine products for consumption and used as material for creative economic activities. But the processing is still traditional. MSME business development must be carried out so that MSME actors can develop their business, namely through product variant development innovations, branding, and digital marketing. The mentoring process in the context of empowering MSME actors must be carried out in order to generate added value for MSME products. Greater added value can play a role in increasing economic growth and have an impact on increasing the welfare of MSME actors.